(untitled) (Revista científica Olimpia, 2021)
The article describes the stages of the historical-tendency analysis of the special schools teachers’ professional improvement process, paying attention to the students’ diagnosis with visual disabilities for the practice of Para-karate. For its analysis, the existences of four main stages were established in the process of these teachers’ professional improvement determined by the assumed theoretic sustenance.